"Come and share a story with me": Promoting engagement between Ethiopian and Non-Ethiopian Israelis via joint digital narratives. (November 2021) - Fachter, Shani; Schiavo, Gianluca; Snider, Keren LG.; Cappelletti, Alessandro; Stock, Oliviero; Weiss, Patrice L.; Zancanaro, Massimo; Canetti, Daphna
Abstract: Does building a collaborative digital story lead to reduction of intergroup tension? Studies show that joint storytelling can help reach deeper levels of understanding through exposure to another group's narrative. We hypothesized that engagement in a collaborative digital storytelling task would lead to reductions of negative emotions and attitudes. In our study, dyads of Ethiopian and non-Ethiopian Israelis interacted via a unique digital platform that supports storytelling in a comics-like format aiming to reduce intergroup tension. Their responses to this task were measured before and after the joint activity. Findings showed a decrease in negative emotional states in intergroup contexts (STAI) between pre-and post-intervention for members of both groups, and a slight decrease in negative attitudes toward the out-group. In other words, joint-digital storytelling sessions lead groups in complex relations to be more likely to support engagement. This study has implications for the effect of contact on intergroup tension. Highlights: Dyads of Ethiopian and non-Ethiopian Israelis interacted via a digital, comics-like format platform that supports storytelling aiming to reduce intergroup tension. Findings show a decrease in negative emotional states in intergroup contexts between pre-and post-intervention for both groups. Findings also show a decrease in negative attitudes toward the out-group among Israeli Ethiopian participants. Joint-digital storytelling sessions lead groups in complex relations to be more likely to support engagement. This study has implications for the effect of contact on intergroup tension.